Experimental Evidence of the Existence of Interleaflet Coupled Nanodomains: An MC-FRET Study - Vinklárek, Ivo S; Vel'as, Lukáš; Riegerová, Petra; Skála, Kristián; Mikhalyov, Ilya; Gretskaya, Natalia; Hof, Martin; Šachl, Radek (The journal of physical chemistry letters, 2019)
Plasma membranes of living cells are compartmentalized into small submicroscopic structures (nanodomains) having potentially relevant biological functions. Despite this, structural features of these nanodomains remain elusive, primarily due to the difficulties in characterizing such small dynamic entities. It is unclear whether nanodomains found in the upper bilayer leaflet are transversally registered with those found in the lower leaflet. Experiments performed on larger microscopic domains indicate that the coupling between the leaflets is strong, forcing the domains to be in perfect registration, but can the same thing be said about the biologically more relevant nanodomains? This work provides experimental evidence that even small nanodomains of variable sizes between 10 and 160 nm are interleaflet coupled. Importantly, the alternative scenarios of partially registered, independent, or antiregistered nanodomains could be excluded.